2021
DOI: 10.3390/biomedicines9101450
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin D Supplementation on Bone Mineral Density and All-Cause Mortality in Heart Transplant Patients

Abstract: Vitamin D (VD) deficiency is frequently reported in heart transplant (HT) recipients and routinely supplemented. However, the efficacy of VD supplementation on bone mineral density (BMD) and its association with all-cause mortality is underinvestigated. The VD levels and BMD were studied for two years, and the association of VD and BMD with all-cause mortality risk was investigated. Ninety-six HT patients (38.18 ± 12.10 years old; 74% men) were followed up during VD, Ca, and Mg supplementation. Anthropometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…2,3 Osteoporosis is one of the important causes of morbidity after lung transplantation, and fractures resulting from it can significantly affect the life expectancy of patients. Numerous studies have documented the degree of bone mass loss that occurs after kidney [4][5][6] , heart 7,8 , and liver [9][10][11] transplantation. Lung transplantation has been associated with a decrease in bone mass index, but there are few studies on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Osteoporosis is one of the important causes of morbidity after lung transplantation, and fractures resulting from it can significantly affect the life expectancy of patients. Numerous studies have documented the degree of bone mass loss that occurs after kidney [4][5][6] , heart 7,8 , and liver [9][10][11] transplantation. Lung transplantation has been associated with a decrease in bone mass index, but there are few studies on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the addition of VD increases peroxisome proliferator-activated receptor gamma (PPAR)-γ1 levels, CPT-1A and ABCA1 proteins, while, by contrast, it blocks the increase in both CD-36 and C/EB proteins induced through FFA administration. Abulmeaty et al [18] reported that VD deficiency is frequently present in heart transplant (HT) patients, but a 2-year supplementation of VD did not seem to have a positive impact on the bone mineral density (BMD). Furthermore, obesity represents an independent risk factor for the onset of cardiovascular diseases, for which vitamin D levels have not appeared to have any positive impact.…”
mentioning
confidence: 99%